Estudo de vetores no ensino médio para resolução de problemas - Chalega, Josimilson de Freitas [UNIFESP] (2018)
This paper presents a proposal to introduce the study of vectors in High School that is motivated by the fact that the time spent with the presentation of vectors for this level is rewarded with greater ease in the approach of some topics, in the resolution of problems and generalization of these solutions. The concept of vector is introduced from both the geometric (collection of equipotential segments) and algebraic (characterized by coordinates) with approaches consistent with the level of High School. Some exercises are presented to compare the resolution of problems without the use of vectors and the use of vectors.